PEMAHAMAN TENTANG KOMUNIKASI DALAM ORGANISASI MERUPAKAN DASAR DALAM MEMBENTUK GAYA KEPEMIMPINAN SESEORANG DALAM SUATU ORGANISASI - Riefky Krisnayana (Dialektika, 2017)
Communication can be seen as a means to channel the social input into the social system. Communication is also a suggestion to modify behavior, affect change, memproduktifkan information and means to achieve the goal. In an organization today, information flows faster. Congestion is very short even in fast moving production lines can lead to large losses due to loss of production. Another important element is the amount of information that is increasingly bloated and often causes the burden of information overload, which is actually needed is not more information, but the information is relevant. Thus necessary to determine the type of information required in the framework of an organization for effective decision making. Organizational communication refers to the patterns and forms of communication that occurs within the context and the organization's network. Organizational communication involves forms of interpersonal communication and group communication. Discussion of organizational communication, among others concerning the structure and functioning of the organization, human relations, communication and organizing processes and organizational culture. Organizational communication is defined as the flow of messages in a network of interdependent nature of his relationship with one another include vertical and horizontal communication flows. How to talk to the other person and how one behaves in front of others is a work style and communication style. Style concept shows that we are dealing with a combination of language and actions, which seem to describe a fairly consistent pattern.